Mapping intermolecular interactions and active site conformations: from human MMP-1 crystal structure to molecular dynamics free energy calculations. Issue 3 (17th February 2017) - Nash, Anthony; Birch, Helen L.; de Leeuw, Nora H.
Abstract : The zinc-dependent Matrix Metalloproteinases (MMPs) found within the extracellular matrix (ECM) of vertebrates are linked to pathological processes such as arthritis, skin ulceration and cancer. Although a general backbone proteolytic mechanism is understood, crystallographic data continue to suggest an active site that is too narrow to encompass the respective substrate. We present a fully parameterised Molecular Dynamics (MD) study of the structural properties of an MMP-1-collagen crystallographic structure (Protein Data Bank – 4AUO), followed by an exploration of the free energy surface of a collagen polypeptide chain entering the active site, using a combined meta-dynamics and umbrella sampling (MDUS) approach. We conclude that the interactions between MMP-1 and the collagen substrate are in good agreement with a number of experimental studies. As such, our unrestrained MD simulations and our MDUS results, which indicate an energetic barrier for a local uncoiling and insertion event, can inform future investigations of the collagen-peptide non-bonded association steps with the active site prior to proteolytic mechanisms. The elucidation of such free energy barriers provides a better understanding of the role of the enzyme in the ECM and is important in the design of future MMP inhibitors.